1998
DOI: 10.1002/(sici)1097-0215(19980529)76:5<628::aid-ijc3>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics, pigmentary and cutaneous risk factors for squamous cell carcinoma of the skin: A case-control study

Abstract: We conducted a case‐control study of squamous cell carcinoma of the skin (SCC) in a cohort of people followed from 1987 to 1994. Subjects were residents of Geraldton, Western Australia, who were between 40 and 64 years of age in 1987. On 2 occasions, in 1987 and 1992, dermatologists examined participants for skin cancers. Subjects were also asked on several occasions about skin cancers that they had had treated. Migrants to Australia had reduced risks of SCC. Furthermore, people who migrated to Australia early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 17 publications
7
92
1
1
Order By: Relevance
“…Individuals who were Australian-born (particularly compared with those born overseas and arriving in Australia after age 20 years) tended to have higher skin damage scores. This is consistent with the finding by English et al of a decreasing risk of squamous cell carcinoma of the skin with later arrival in Australia compared with Australian-born (26). In contrast to other studies, we found no association with smoking (12), body mass index (16), or intake of antioxidants (assessed by dietary supplement history; ref.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals who were Australian-born (particularly compared with those born overseas and arriving in Australia after age 20 years) tended to have higher skin damage scores. This is consistent with the finding by English et al of a decreasing risk of squamous cell carcinoma of the skin with later arrival in Australia compared with Australian-born (26). In contrast to other studies, we found no association with smoking (12), body mass index (16), or intake of antioxidants (assessed by dietary supplement history; ref.…”
Section: Discussionsupporting
confidence: 91%
“…However, with the exception of actinic keratoses, the associations were modest and the strength of association was similar to that found for self-reported cumulative sun exposure. This is in contrast with SCC where the presence of actinic keratoses increases risk by 30 to 40 times and telangiectasia and solar elastosis confer 3-and 6-fold increases in risk, respectively (46,52). These relatively lower associations with BCC might suggest that different patterns of sun exposure such as intense exposure are important.…”
Section: Discussionmentioning
confidence: 89%
“…Sunlight is considered the main etiologic factor for SCC of the skin with wavelengths in the UV light B spectrum (UV-B, wavelengths between 280 and 320 nm) most associated with SCC risk (11). Although geographic comparisons of SCC data suggest that differences in UV-B exposure may account for some of the differences in SCC incidence, preventive agents, or enhancing factors may also be important (12).…”
Section: Introductionmentioning
confidence: 99%